2011
DOI: 10.4103/0973-6131.78171
|View full text |Cite
|
Sign up to set email alerts
|

Neurohemodynamic correlates of ′OM′ chanting: A pilot functional magnetic resonance imaging study

Abstract: Background:A sensation of vibration is experienced during audible ‘OM’ chanting. This has the potential for vagus nerve stimulation through its auricular branches and the effects on the brain thereof. The neurohemodynamic correlates of ‘OM’ chanting are yet to be explored.Materials and Methods:Using functional Magnetic Resonance Imaging (fMRI), the neurohemodynamic correlates of audible ‘OM’ chanting were examined in right-handed healthy volunteers (n=12; nine men). The ‘OM’ chanting condition was compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…[33] In a previous study on neurohemodynamic correlates of “OM” chanting showed limbic deactivation and similar observations were recorded in vagal nerve stimulation used in the treatment of depression,[34] which is common in COPD, bronchial asthma and can affect the quality of sleep, quality-of-life and diseases condition. [353637]…”
Section: Discussionmentioning
confidence: 59%
“…[33] In a previous study on neurohemodynamic correlates of “OM” chanting showed limbic deactivation and similar observations were recorded in vagal nerve stimulation used in the treatment of depression,[34] which is common in COPD, bronchial asthma and can affect the quality of sleep, quality-of-life and diseases condition. [353637]…”
Section: Discussionmentioning
confidence: 59%
“…It also enables the development of mindfulness of the 'present moment' thus potentiating self-control over one's thoughts, feelings and actions [23]. A novel study by Kalyani et al [36], studied hemodynamic correlates of 'OM' chanting and reported that it produced limbic deactivation. They observed significant deactivation bilaterally during 'OM' chanting in comparison to the resting brain state in orbito-frontal, anterior cingulate, parahippocampalgyri thalami and hippocampi.…”
Section: Discussionmentioning
confidence: 99%
“…In Yoga, the role of OM sound is considered as a soothing, relaxing and unbroken thought to meditate upon (Kumar et al, 2010). Neuroimaging study on chanting of "OM" sound suggests the involvement of limbic system such as left anterior cingular cortex (ACC) and amygdale (Kalyani et al, 2011). These regions are involved in assessing the salience of emotional and motivational information and the regulation of emotional responses (Bush, Luu, & Posner, 2000).…”
mentioning
confidence: 98%
“…These regions are involved in assessing the salience of emotional and motivational information and the regulation of emotional responses (Bush, Luu, & Posner, 2000). Kalyani et al (2011) suggested that "OM" chanting may also have confounding effect on relaxation based on the cortical structures observed in the study.…”
mentioning
confidence: 99%